Traditional Heritage in the Collection of Poems Bunjevački Blues (2003) by Tomislav Žigmanov - Markasović, Vlasta (Anafora, 2023)
Tomislav Žigman is an author who belongs to the mainland, northern and Pannonian sections of the literary corpus, according to many world-philosophical, traditional-cultural and linguistic determinants of his work. Bunjevački blues is a collection of lyric songs / letters, which was released in two editions. This article deals with the second, extended edition from 2003. (Subotica). The collection is based on Bunjevci traditionalcultural stock such as linguistic heritage, traditional life, worldview and mentality characteristics, a clash of traditional and modern etc. First of all, these stocks are implied and visible in the motif-themed layer, which is absolutely rooted in the ikavian dialect of Bunjevci. Therefore, the article partly focuses on the stylistic stigmatization of the Bunjevci ikavian and and lexical forms in the rhythmic, melodic and semantic fabric of the poetic text. In addition, the traditional stimuli in the philosophical consciousness of the poem and the motif-thematic fabric of the poem are questioned, which give it quite characteristic features and make it a representative work of the Pannonian literary circle. An attempt is made to detect the inspirational and affective springs that lead the text to regional colourfulness and to establish a process of nuance of traditional and mentality specificities. Particularly noteworthy is the title entry, which is woven into poetic texts as a thought leitmotif and atmosphere omen, thus stimulating the recipient’s horizon of expectation, inaugurating the text as a melancholy cantilena and referring to a commonly known musical jeremiad.